Analisis Teknik Penerjemahan Sulih Suara Film Lesson For An Assassin Di JTV - UMMATIN, KHOIRU (Kementerian Sekretariat Negara Republik Indonesia, 2015)
The aim of this research is to describe the translation technique used by the translator in translating the subtitle in Indonesian and the dubbing in Suroboyoan Javanese of the Lesson for An Assassin film. The result shows that the translator uses eight translation techniques, namely the paraphrase, transfer, imitation, condensation, deletion, taming and resignation techniques. By degree of frequency, the most frequently used techniques are the transfer with 255 data (46.9%), paraphrase: 176 data (32.4%), imitation: 65 data (11.9%), expansion: 40 data (7.4%), resignation: 28 data (5.2%), deletion: 15 data (2.8%), condensation: 13 data (2.4%), and taming: 2 data (0.36%). Keywords: translation techniques, dubbing, film